Exercise, immunity, and susceptibility to infection - Shephard, R. J.; Shek, P. N. (The Physician and Sportsmedicine, 1999)
Regular, moderate exercise enhances immune function and attenuates immune disturbances associated with acute exercise (ie, a single bout of vigorous exercise). Epidemiologic data suggest that vigorous exercise may temporarily reduce resistance to viral infection. However, objective data do not clearly show a J-shaped dose-response relationship between exercise and immune function. Nutritional, hygienic, exercise, environmental, and pharmacologic strategies can minimize the risk of infection. Persons who have systemic symptoms should avoid competition and heavy training.